Two new species of Hilara (Diptera, Empididae) from northwestern Turkey - Çiftçi, Mustafa Cemal; Hasbenli, Abdullah (Zootaxa, 2011)
Two new species, Hilara deryae sp. nov. (Hilara clavipes-group) and Hilara hasankoci sp. nov. (Hilara interstincta- group) are described from northwestern Turkey. The male and female stages are described, compared with related species and male genitalia and forelegs illustrated. Keys to the western Palaearctic species of Hilara clavipes-group and the Mediterranean species of Hilara interstincta-group are updated. Also the systematic position of the new species within the species groups is discussed.